Sense of coherence versus health behaviour of people qualified for cardiosurgical operation - Kurowska, Krystyna; Trzeciak, Dominika; Głowacka, Mariola; Ponczek, Danuta (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2010)
Introduction : Sense of coherence is a construct that explains the connection of health behaviour with health. High sense of coherence gives a faith in the meaning of life, its order, predictability – which brings about willingness to be healthy and function proficiently. The aim of the research was to gauge the level of the sense of coherence and health behaviour of the patients hospitalized due to cardiosurgical operation. Material and methods : Sixty-six patients from Cardiosurgery Clinic of University Hospital number 1 in Bydgoszcz were examined. Sense of coherence was evaluated by means of questionnaire SOC-29 and health behaviour measurement – Health Behaviour Inventory. Results : Examined patients did not differ from each other in sense of coherence and health behaviour, however they were significantly different as far as the level of resourcefulness, healthy eating habits, preventive behaviour and health practices are concerned. Conclusions : Received results may serve as educational material for medical personnel in order to initiate modification in patient’s life style who suffer from circulatory system ailments. It may also be useful to appropriate preparation of patients for cardiosurgical operation, especially the psychical sphere because this sphere plays a significant role.